PENINGKATAN PERILAKU NASABAH TABUNGAN LEMBAGA KEUANGAN MIKRO SYARIAH MELALUI PENGGUNAAN LAYANAN MOBILE - Muhammad Muflih (Ekonis: Jurnal Ekonomi dan Bisnis, 2019)
Abstrak: An increase in the number of well-behaved savings customers is a very important strategy choice for the Sharia Microfinance Institution (LKMS) today. In the context of the relationship between the use of mobile services and the improvement of LKMS savings customer behavior, the literature does not pay attention. This study examines the behavior of LKMS savings customers (SAV) with three determinants, namely the use of mobile services (MOB), trust (TRU), and satisfaction (SAT). By utilizing the results of a survey of 200 samples of LKMS customers in Bandung and West Bandung districts, this study conducted an SEM-PLS analysis. Estimation results prove that MOB has a positive effect on SAV both directly and with TRU and SAT mediation. This study highlights the importance of MOB optimization for the progress of the SAV level in LKMS. In the final section, this study presents the theoretical and managerial implications. Keyword: Use of mobile services, trust, satisfaction, savings customer behavior, LKMS, SEM-PLS